The effect of metabolic comorbidities and commonly used drugs on the prognosis of patients with ovarian cancer. (December 2016) - Bar, Daniel; Lavie, Ofer; Stein, Nili; Feferkorn, Ido; Shai, Ayelet
Abstract: Background: Diabetes mellitus is associated with an increased risk of recurrence in patients with ovarian cancer. Retrospective studies suggested that the use of statins, metformin and beta blockers is associated with improved prognosis in these patients. Patients with diabetes often suffer from hypertension and are usually treated concomitantly by several classes of drugs. Our aim was to assess the independent contribution of diabetes mellitus and hypertension and of the use of aspirin, statins, metformin and beta blockers on the risk of ovarian cancer recurrence and mortality. Methods: Files of ovarian cancer patients treated between 2000 and 2012 were retrospectively reviewed. Data regarding disease characteristics, presence of diabetes mellitus and hypertension, recurrence and death were extracted. The use of drugs was assessed using the Clalit Health Services (CHS) pharmacy records. Results: 143 patients treated by debulking surgery and platinum based chemotherapy were included. Median age was 62.5, 22 (15.4%) had diabetes mellitus, 61 (42.7%) had chronic hypertension. Statins were used by 43 (30%) patients, 31 (21.7%) used aspirin, 25 (17.5%) used beta blockers and 12 (8.4%) used metformin. In multivariate analysis diabetes mellitus was associated with a shorter recurrence free survival (RFS) and the use of aspirin and metformin was associated with a prolonged RFS in this cohort. Overall survival (OS) was longer in patients using aspirin and shorter in patients with hypertension. Conclusions: Our data suggests that metabolic comorbidities and commonly used drugs are associated with the prognosis of patients with ovarian cancer. Additional trials are needed to confirm these observations and test therapeutic interventions.